2017
DOI: 10.1016/j.neuint.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of CD74 and its potential association with disease severity in subjects with ischemic stroke

Abstract: Macrophage migration inhibitory factor (MIF) is a key cytokine/chemokine in the activation and recruitment of inflammatory T lymphocytes known to exacerbate experimental stroke severity. MIF effects are mediated through its primary cellular receptor, CD74, the MHC class II invariant chain present on all class II expressing cells, including monocytes, macrophages and dendritic cells (DC). We demonstrated previously that partial MHC class II/peptide constructs (pMHC) can effectively treat mice with experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…SIRS is indicated by abnormal leukocyte counts, high respiratory and heart rate (>90 bmp), and abnormal body temp, and can increase the risk of developing vasospasm and secondary complications 117 . In ischemic stroke patients, the number of CD74 + cells (the MHC class II invariant chain present on all class II expressing cells, including monocytes, macrophages and dendritic cells) were significantly increased in peripheral blood mononuclear cells compared to healthy controls 118 . The increased CD74 positive cells were mainly on CD4 + T cells, monocytes and dendritic cells 118 .…”
Section: Mechanisms Of Brain-heart Interaction After Strokementioning
confidence: 96%
See 1 more Smart Citation
“…SIRS is indicated by abnormal leukocyte counts, high respiratory and heart rate (>90 bmp), and abnormal body temp, and can increase the risk of developing vasospasm and secondary complications 117 . In ischemic stroke patients, the number of CD74 + cells (the MHC class II invariant chain present on all class II expressing cells, including monocytes, macrophages and dendritic cells) were significantly increased in peripheral blood mononuclear cells compared to healthy controls 118 . The increased CD74 positive cells were mainly on CD4 + T cells, monocytes and dendritic cells 118 .…”
Section: Mechanisms Of Brain-heart Interaction After Strokementioning
confidence: 96%
“…In ischemic stroke patients, the number of CD74 + cells (the MHC class II invariant chain present on all class II expressing cells, including monocytes, macrophages and dendritic cells) were significantly increased in peripheral blood mononuclear cells compared to healthy controls 118 . The increased CD74 positive cells were mainly on CD4 + T cells, monocytes and dendritic cells 118 . In heart diseases such as myocardial infarction, elevation of circulating blood monocytes is associated with poor cardiac function and predicts poor recovery of left ventricular systolic function at 3 months post injury 119 .…”
Section: Mechanisms Of Brain-heart Interaction After Strokementioning
confidence: 96%
“…In addition, partial MHC class II constructs were shown to reverse stroke-associated splenic atrophy and promote a protective anti-inflammatory macrophage/microglia phenotype in the CNS which contributes to tissue repair and recovery after stroke [59, 60]. A recent study has also demonstrated increased expression of CD74 on T cells and antigen-presenting cells that directly correlate with infarct size and neurological deficits in people with ischemic stroke [61].…”
Section: Introductionmentioning
confidence: 99%
“…* p < 0.05, ** p < 0.01. Reprinted by permission from RightsLink: Springer, Translational Stroke Research, DRα1-MOG-35-55 treatment reduces lesion volumes and improves neurological deficits after traumatic brain injury, Yang et al, copyright 2017 [61]…”
Section: Introductionmentioning
confidence: 99%
“…These monocytes, also through their increased secretion of IL-10 and downregulation of human leukocyte antigen-DR isotype (HLA-DR) thus acquire an immune suppressed state (16, 17, 33, 46, 5254). That said, CD74, the invariant polypeptide chain associated with the HLA complex is upregulated in the peripheral blood mononuclear cells of patients (55). Despite being capable of processing and transporting antigens, monocytes, nevertheless, are not professional antigen-presenting cells (56, 57).…”
Section: The Systemic Immune Landscape Of Strokementioning
confidence: 99%